Estimation in periodic restricted EXPAR(1) models. Issue 10 (26th November 2018) - Merzougui, M.
ABSTRACT: This article is devoted to study the problem of estimation in the periodic restricted exponential autoregressive EXPAR(1) models. The estimation procedure that is used is the least-square method. Simulation studies are carried out in order to check the asymptotic properties. An application to monthly flow data for the Fraser River in British Columbia is included.